The benefits of role play in the development of drawing in preschool children - Bonilla-Sánchez, María del Rosario; García-Flores, Marco Antonio; Méndez-Balbuena, Ignacio; Silva-González, Jocelyn Guadalupe; Ramírez-Arroyo, Ernesto Vladimir (Frontiers in Psychology, 2022)
The role play is a key activity for the development of significant psychological processes such as the symbolic function which allows the children to substitute concrete objects with symbolic representations. So, as the children are able to substitute more elements during role play, they are capable of represent mentally missing objects and produces novel forms of behavior. On the other hand, drawing requires, in its formation, the capacity to substitute the essential characteristics of the object trough a symbolic perceptive action. Both, role play and drawing allow the children to better control their psychological processes. The objective of the study is to show the benefits of role play with symbolic elements in the development of drawing of preschool children from suburban origin. A program was designed to develop the drawing process through role play in a suburban group of preschool children. The results show significant differences in drawing before and after the role play program.